Feasibility and acceptability of offering rapid HIV tests to patients registering with primary care in London (UK): a pilot study. Issue 5 (31st May 2009) - Prost, A; Griffiths, C J; Anderson, J; Wight, D; Hart, G J
Abstract : Objective: To assess the acceptability and feasibility of offering rapid HIV tests to patients registering with primary care in London, UK. Methods: All Anglophone and Francophone patients aged between 18 and 55 years attending a large inner city general practice in London for a new patient health check were recruited. All eligible patients were offered a rapid HIV test on oral fluid and asked to participate in a qualitative interview. The uptake of rapid HIV testing among participants was measured and semistructured interviews were carried out focusing on the advantages and disadvantages of testing for HIV in primary care. Results: 111 people attended the health check, of whom 85 were eligible, 47 took part in the study and 20 completed qualitative interviews. Nearly half of eligible participants (38/85, 45%) accepted a rapid HIV test. The main reason for accepting a test was because it was offered as "part of a check up". As a combined group, black African and black Caribbean patients were more likely to test in the study compared with patients from other ethnic backgrounds (p = 0.014). Participants in the qualitative interviews felt that having rapid HIV tests available in general practice was acceptable but expressed concerns about support for the newly diagnosed. Conclusions: Offering patients a rapid HIV test in primary care is feasible and could be an effective means to increase testing rates in this setting. A larger descriptive study or pragmatic trial is needed to determine whether this strategy could increase timely diagnosis and reduce the proportion of undiagnosed HIV infections in the UK.